Patron-client and Lindu lake tourism development - Hasan Muhamad; Moh Saleh; Andi Mascunra (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Lindu Lake in Lore Lindu National Park, Sigi Regency, spatially has characteristics and potential as a coastal area that migrants enter along with the culture it inhabits and there are socio-cultural changes in the local community. From the background of the aforementioned problems, the objectives of the study are as follows: 1) to see the relationship between financiers (Patrons) and local fishermen (clients) in Lindu Lake; 2) fishermen's support for the arrangement of their settlements as homestays; and 3) a model of integration of fishing settlement space with ecological-based coastal tourism. This research uses a qualitative research approach (phenomenological paradigm) with analytical descriptive methods. The results showed, as follows: (1) The relationship between financiers and local fishermen in Lindu Lake is nothing more than borrowing business capital; (2) Fishermen's support for the arrangement of their settlement as a homestay, this is due to the large number of tourists at the festival but the benefits are not felt; (3) The integration model of fishing settlement space with ecological-based coastal tourism with consideration of the development of marine tourism in Lindu Lake is integrated between mountain and lake panoramas with customs into one unit.